The Learning Revolution: Impacting Curriculum, Assessment and Pedagogical Strategies in Higher Education - Philips, John Arul (2017)
The learning revolution brought about by the rapid growth of internet tools and technologies, digital content and mobile devices calls for a transformation of higher education. The paper examines how the learning revolution is reshaping what we teach (or curriculum), how we teach (or pedagogical strategies) and how we assess learning (or assessment). The rise of MOOCs, OERs and access to massive amounts of digital content has triggered the need to re-evaluate what we teach. Similarly,various internet technologies, artificial intelligence and mobile devices has prompted the need to exploit how we teach. Technological innovations, learning analytics and platforms has provided insight into how to holistically assess learner performance using an assortment of tools. The authors illustrate with examples how the learning revolution impacts curriculum, pedagogy and assessment in their institution such as access to remote areas, adapting to low language proficiency, motivating adult learners, assessing learning and others.